Biomarkers for Radiation Biodosimetry and Injury Assessment after Mixed-field (Neutron and Gamma) Radiation in the Mouse Total-body Irradiation Model. Issue 6 (December 2018) - Ossetrova, Natalia I.; Stanton, Paul; Krasnopolsky, Katya; Ismail, Mohammed; Doreswamy, Arpitha; Hieber, Kevin P.
Abstract : Abstract: The risk of potential radiation exposure scenarios that include detonation of nuclear weapons, terrorist attacks on nuclear reactors, and the use of conventional explosives to disperse radioactive substances has increased in recent years. The majority of radiation biodosimetry and countermeasure studies have been performed using photon radiation even though many exposure scenarios predict mixed-field (neutron and photon) radiation. Hence, there is a need to evaluate biomarkers and accurately determine exposure levels of mixed-field combinations of neutrons and photons for an individual. These biomarkers will be critical for biodosimetry triage, treatment, and follow-up visits with such individuals. We evaluated the utility of multiple blood biomarkers for early response assessment of radiation exposure using a mouse (B6D2F1, males and females) total-body irradiation model exposed to a mixed-field (neutrons and gamma rays) using the Armed Forces Radiobiology Research Institute's Mark F nuclear research reactor. Total-body irradiation was given as a single exposure over a dose range from 1.5 to 6 Gy, dose rates of 0.6 and 1.9 Gy min ‐1, and different proportions of neutrons and gammas: either (67% neutrons + 33% gammas) or (30% neutrons + 70% gammas). Blood was collected 1, 2, 4, and 7 d after total-body irradiation. Radiation-responsive protein biomarkers were measured using the Meso Scale Diagnostics' high-throughput MULTI-ARRAY plate-format platform (QuickPlex 120 Imager) and enzyme-linked immunosorbent assay kits. Results demonstrate (1) dose- and time-dependent changes in fms-related tyrosine kinase 3 ligand, interleukins IL‐5, IL‐10, IL‐12, and IL‐18, granulocyte and granulocyte-macrophage colony-stimulating factors, thrombopoietin, erythropoietin, acute-phase proteins (serum amyloid A and lipopolysaccharide binding protein), surface plasma neutrophil (CD45) and lymphocyte (CD27) markers, ratio of CD45 to CD27, and procalcitonin; (2) dose- and time-dependent changes in blood cell counts (lymphocytes, neutrophils, platelets, red blood cells, and ratio of neutrophils to lymphocytes); (3) levels of IL‐18, granulocyte and granulocyte-macrophage colony-stimulating factors, serum amyloid A, and procalcitonin were significantly higher in animals irradiated with 67% neutrons + 33% gammas compared to those irradiated with 30% neutrons + 70% gammas ( p < 0.015), while no significant differences ( p > 0.114) were observed in hematological biomarker counts; (4) exposure with 3‐fold difference in dose rate (0.6 or 1.9 Gy min −1 ) revealed no significant differences in hematological and protein biomarker levels ( p > 0.154); and (5) no significant differences in hematological and protein biomarker levels were observed in the sex-comparison study for any radiation dose at any time after exposure ( p > 0.088). Results show that the dynamic changes in the levels of selected hematopoietic cytokines, organ-specific biomarkers, and acute-phase protein biomarkers reflect the time course and severity of acute radiation syndrome and may function as prognostic indicators of acute radiation syndrome outcome. These studies supplement an ongoing effort to deliver U.S. Federal Drug Administration-approved biodosimetry capabilities, which assess mixed-field radiation exposure. Abstract : Supplemental digital content is available in the text.